Determinants maintaining healthcare personnel’s motivation during COVID-19 pandemic in Uganda - Makiko Komasawa; Myo Nyein Aung; Christopher Nsereko; Kiyoko Saito; Robert Ssekitoleko; Mitsuo Isono; Motoyuki Yuasa (Scientific Reports)
Abstract Background Maintaining the physical and psychological well-being of healthcare workers (HCWs) is crucial for health system resilience. In sub-Saharan Africa, particularly Uganda, HCWs faced significant challenges during the coronavirus disease 2019 (COVID-19) pandemic, compounded by pre-existing resource constraints. This study investigated challenges faced by HCWs at a designated COVID-19 hospital (‘the Hospital’) and explored determinants of maintaining healthcare personnel’s motivation during the COVID-19 pandemic in Uganda. Methods A facility-based cross-sectional study was conducted at the Hospital from May to July 2023, with 120 HCWs categorised by profession. Data were collected using a structured questionnaire. Descriptive and logistic regression analyses were performed to identify motivation-related factors. The questionnaire assessed sociodemographic data, COVID-19 knowledge, medical history, support received, and pandemic-related challenges. Psychological impact was measured using a four-point Likert scale. Results Among respondents, 61.7% worked during the first lockdown and 93.3% during the second. COVID-19 knowledge was high, with over 70% answering questions correctly, although vaccine effectiveness had a slightly lower accuracy rate. The study revealed that 32.5% of HCWs tested positive for COVID-19 and 25% displayed vaccine hesitancy. Key challenges included fear of infection, transportation disruptions, income reduction, and social isolation. Notably, 92.5% reported significant anxiety related to infection. Factors positively associated with remaining motivated were age (≤ 30 versus > 30 years; adjusted odds ratio [AOR]: 10.34, 95% CI; 1.92–55.74), profession (co-medical/non-medical staff versus medical doctors/medical officers; AOR: 11.66, 95% CI: 1.03–132.22), receiving mentoring/tutoring (AOR: 18.87, 95% CI: 2.55–139.72), and information from supervisors/management (AOR: 12.5, 95% CI: 2.60–60.42). In contrast, psychological impact was negatively affected by isolation from family and friends (AOR: 0.61, 95% CI: 0.41–0.92). Conclusions Despite challenges, most HCWs at the Hospital remained motivated. These findings emphasised the importance of technical and psychological support, such as mentoring and effective communication from upper-level supervisors, rather than financial incentives, in maintaining motivation among the HCWs. Comprehensive support systems are essential for sustaining HCWs’ motivation during the pandemic, especially in resource-limited settings. Further research should address the long-term mental health effects and enhance HCWs’ resilience in future health crises.